2019
DOI: 10.3390/coatings9030182
|View full text |Cite
|
Sign up to set email alerts
|

Dental Resin-Zirconia Bonding Promotion Using High-Silica PVD Coating with High Ionization Sputtering Processing

Abstract: Purpose: To evaluate the effect of high-silica coating deposited by high-silica physical vapor deposition (PVD) as a chemical bonding method on resin-zirconia bond strength under different aging conditions. Methods: Twelve Y-TZP blocks were used as the substrates. Four resin cement stubs were bonded on each Y-TZP block, with a total number of 48 resin cement stubs. Two test groups (n = 24) were evaluated: conventional Tribochemical silica-coating (TSC) and high-silica PVD with high ionization sputtering proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The combinations of MDP cement with MDP primer and Non-MDP cement with MDP primer showed negative mean pooled difference. In cases where treatments other than SA or TSC were used (no SA + OST) in the shear test group, 3 studies using a non-MDP cement + non-MDP primer [128] , [131] or non-MDP cement + no primer [130] presented a non-significant increase in the bond strength after aging ( Fig. 2 D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combinations of MDP cement with MDP primer and Non-MDP cement with MDP primer showed negative mean pooled difference. In cases where treatments other than SA or TSC were used (no SA + OST) in the shear test group, 3 studies using a non-MDP cement + non-MDP primer [128] , [131] or non-MDP cement + no primer [130] presented a non-significant increase in the bond strength after aging ( Fig. 2 D).…”
Section: Resultsmentioning
confidence: 99%
“…In cases where TSC was applied only (TSC+NOST), 11 out of 23 studies in the shear test group showed no significant difference of the bond strength after aging ( Fig. 3 A, Table 2 ), while 2 studies [94] , [131] showed slight increase in bond strength. Mean pooled difference showed significant decrease in most of the cement/primer combination groups irrespectively of the aging process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncertain which cement is optimal as there are some contradictory results on the effect of types of cement on fracture load in previous studies [ 11–13 ]. Furthermore, there is limited evidence regarding the best method of pre-treating the zirconia surfaces for optimal bonding [ 12 , 14 , 15 ]. Some studies have shown that enhanced adhesion can be achieved through mechanical and chemical surface treatments such as airborne particle abrasion (air-abrasion), tribochemical silica coating, or the use of phosphate groups in the bonding or cement [ 12 , 14–17 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the content of CaSi in the ZrO 2 matrix was 20 wt %, the chemical bond originating from ion diffusion after firing may have been the reason for the high interfacial strength [31]. Due to the formation of -Si-O-Si-bonds [32], silica has been proven to be a very important factor in enhancing bond strength [8,21]. Liu et al infiltrated glass into ZrO 2 and improved the bond strength of the ceramic veneer-core by ion diffusion-induced chemical bonding [33].…”
Section: Discussionmentioning
confidence: 99%